A P2/P3 composite layered cathode for high-performance Na-ion full batteries. (January 2019) - Zhou, Ya-Nan; Wang, Peng-Fei; Niu, Yu-Bin; Li, Qinghao; Yu, Xiqian; Yin, Ya-Xia; Xu, Sailong; Guo, Yu-Guo
Abstract: Na-ion batteries (NIBs) have been suggested as one of the most promising technologies for low-cost rechargeable batteries due to the earth-abundance resource of sodium. However, the delivery of high-performance cathode is still facing a great challenge especially for the development of Na-ion full batteries towards practical application. Herein, we present a layered biphasic cathode with P2 and P3 integrated structures, which is clearly elucidated by X-ray diffraction refinement, high resolution transmission electron microscopy and selected area electron diffraction. Combining the respective characteristics of P2 and P3 phases and highly reversible P2/P3–P2/OP4 structural evolution, the layered composite delivers a high reversible capacity of 119 mA h g −1 with a superior initial Coulombic efficiency of 94.8%, a high operating voltage of 3.53 V vs Na + /Na based on Ni 2+ /Ni 4+ redox couple, and an outstanding rate performance (capacity retention of 85.5% at 5C compared with 0.2C). Furthermore, the assembled Na-ion full battery of P2/P3-Na0.7 Li0.06 Mg0.06 Ni0.22 Mn0.67 O2 //hard carbon exhibits a high average voltage of 3.36 V with a calculated energy density up to 218 W h kg −1 . Our contribution paves a smart way for designing sodium-ion full batteries with both high energy density and good cycling stability toward practical application. Graphical abstract: P2/P3-Na 0.7 Li 0.06 Mg 0.06 Ni 0.22 Mn 0.67 O 2 composite cathode integrating the structural advantages of P2 and P3 phases is synthesized through the temperature-induced P3–P2 phase transition. The Na-ion full cell with P2/P3-NLMNM//hard carbon exhibits a high working voltage of 3.36 V (vs Na + /Na) with energy density up to 218 W h kg −1 .fx1 Highlights: Novel layered P2/P3 biphasic structure is prepared by monitoring phase evolution. The integrated cathode exhibits an enhanced capacity retention and rate performance via a reversible P2/P3–OP4/P3 phase transition. Charge compensation mechanism is revealed by ex situ XANES and EXAFS. Na-ion full battery delivers a high average voltage (3.36 V) and energy density (218 W h kg –1 ).